Tindak Tutur Direktif dalam Ceramah Ustadz Hannan Attaki “Kalo Aku Dijahatin, Aku Harus Apa?” - Wahyuni, Tuti; Yuwantika, Diva; F, Fatmawati (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
This study aims to explain the types and purposes of directive speech acts contained in Ustadz Hannan Attaki's lecture entitled "If I'm Harmed, What Should I Do?" This study adopted a descriptive qualitative method with a focus on pragmatics. The data source came from lecture recordings posted on the YouTube platform, while the data analyzed were utterances containing directive speech acts. Data collection was carried out by listening, recording, and taking notes, then the data were analyzed using an interactive analysis model that includes data reduction, data presentation, and drawing conclusions. The results of this study indicate that Ustadz Hannan Attaki's lecture contains various types of directive speech acts, such as prohibitions, advice, and commands. The functions of these directive speech acts include preventing or prohibiting certain actions, providing advice and guidance to listeners, and directing listeners to take actions that are considered positive and useful. These findings indicate that directive speech acts have a significant role in conveying persuasive da'wah messages and increasing listeners' moral awareness.